ON THE ORIGINS OF COSTA RICA´S FIRE DEPARTMENT, 1865-1908 - Quirós Castro, Rodrigo (2016)
The following article discusses the historical conditions under which it became necessary to have a Fire Department in Costa Rica, linking the emergence of institutions of first response to the dynamics of capitalist modernization that affected the social-historic formation Costa Rica during the century nineteenth and early twentieth centuries. Also it refers to conditions that prevented the consolidation of the institution during the nineteenth century mainly. Finally, it inquires about the dynamics of the founding of fire stations and raises some answers as to their closures.